Adverse Impact of Sleep Restriction and Circadian Misalignment on Autonomic Function in Healthy Young Adults. Issue 1 (July 2016) - Grimaldi, Daniela; Carter, Jason R.; Van Cauter, Eve; Leproult, Rachel
Abstract : Insufficient sleep and circadian rhythm disturbances have been each associated with adverse cardiovascular outcomes in epidemiological studies, but experimental evidence for a causal link is scarce. The present study compares the impact of circadian misalignment (CM) to circadian alignment (CA) on human autonomic function using a nonrandomized parallel group design to achieve the same total sleep time in both conditions. After baseline assessments (3 days with 10-hour bedtimes), 26 healthy young adults were assigned to sleep restriction (SR; eight 5-hour bedtimes) with either fixed nocturnal bedtimes (CA; n=13) or bedtimes delayed by 8.5 hours on 4 of the 8 days (CM; n=13). Daytime ambulatory blood pressure and heart rate (HR; CA, n=11; CM, n=10) and 24-hour urinary norepinephrine levels (CA, n=13; CM, n=13) were assessed at baseline and the end of SR. Nocturnal HR and HR variability were analyzed during sleep at baseline and during the fourth and seventh nights of SR (CA, n=8; CM, n=12). SR resulted in a significant increase in daytime HR in both groups, without changes in blood pressure. SR increased 24-hour urinary norepinephrine in the CM group (30±4 versus 21±2 μg), but not in the circadian alignment group (group×condition, P =0.005). In contrast to the lack of detectable impact of CM on daytime autonomic function, SR with CM elicited greater increases in nocturnal HR, as well as greater reductions in vagal indices of HR variability, than SR without CM (group×condition, P <0.05). In conclusion, SR and CM both result in impaired autonomic function that could lead, under chronic conditions, to enhanced cardiovascular risk. Abstract : Supplemental Digital Content is available in the text.